2020
DOI: 10.17533/10.17533/udea.redin.20190403
|View full text |Cite
|
Sign up to set email alerts
|

Fibre reinforced concrete containing waste coconut shell aggregate, fly ash and polypropylene fibre

Abstract: The aim of this study is to investigate the effect of polypropylene fibre addition into eco-concrete made with fly ash, an industrial by product, as partial cement replacement material, and coconut shell, an agricultural waste,  as coarse aggregates, on the mechanical properties of the concrete. Two different mixes were developed, one with coconut shell only as coarse aggregates, and the other with the combination of both conventional aggregates and coconut shell as coarse aggregates. The cement content was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…Gunasekaran et al 15 demonstrated that when subjected to torsion coconut shell concrete beams behaved similarly to normal concrete. The fracture toughness and mechanical attributes of coconut Shell concrete are practically identical to lightweight concrete 8 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Gunasekaran et al 15 demonstrated that when subjected to torsion coconut shell concrete beams behaved similarly to normal concrete. The fracture toughness and mechanical attributes of coconut Shell concrete are practically identical to lightweight concrete 8 .…”
Section: Introductionmentioning
confidence: 90%
“…Thus, the successful usage of agricultural wastes, as a substitute for normal aggregates, contributes to the preservation of depleting resources which is non-renewable, decreases utilization of energy, and also decreases the expenses of construction materials. Authors has utilized a few scrap matters in concrete, with recycled aggregate, fly ash, silica fume waste elastic tire, and GGBFS and waste and glass plastics 8 , 9 . Moreover, tobacco wastes, coconut shell (CS), rice husk ash, palm shell, pistachio shell, oil palm shell (OPS), utilized to deliver lightweight aggregate concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The concave part of CS is smooth, which results in the good workability of CS concrete. Higher impact and abrasion resistance in CS aggregate have been reported in comparison with conventional coarse aggregate 15 . Olanipekun et al 16 reported that an increased content of CS coarse aggregate reduced the cost of concrete mix but slightly reduced the compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…The split tensile strength of SCC2 was increased up to 17 % by the addition of sisal fiber. It can be noticed that the addition of sisal fiber increases the tensile strength up to 8% and this may be attributed by bridging mechanism of fiber (Prakash, 2020).…”
Section: Split Tensile Strengthmentioning
confidence: 95%